Bayer process red mud-based composite pellet binder, preparation method thereof and iron ore pellet

By using microwave-ultrasound synergistic activation to combine Bayer process red mud with slag powder, nano-SiO2, sodium lignosulfonate, and ammonium formate, the problems of insufficient activity of Bayer process red mud and reduced mineral powder grade were solved. A high-performance composite pellet binder was prepared, which improved the strength of green pellets and roasted pellets and reduced mineral powder grade loss.

CN121674696APending Publication Date: 2026-03-17CHALCO SHANDONG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511892581.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-16
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

In existing technologies, Bayer process red mud is used directly as a binder when it has insufficient active ingredients, low strength and large fluctuations. Traditional red mud-bentonite composite binders have failed to effectively solve the problem of reduced mineral powder grade, and the activity improvement of single microwave-activated red mud is limited.

Method used

A high-performance composite pellet binder was formed by microwave-ultrasound synergistic activation treatment of Bayer process red mud, and then compounded with a mixture of slag powder, nano-SiO2, sodium lignosulfonate and ammonium formate in a specific ratio. The activity and strength of the binder were improved through synergistic hydration reaction and dispersion.

Benefits of technology

A high-performance composite pellet binder was prepared, with a green pellet drop strength of ≥4 times/0.5m and a compressive strength of ≥180N/pellet after calcination. It also reduced the impact on mineral powder grade, thus achieving high-strength and low-cost pellet production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of metallurgical binders, and particularly relates to a Bayer process red mud-based composite pellet binder, a preparation method thereof and iron ore pellets. The invention relates to a water-based adsorbent, which is prepared from the following components in percentage by mass: 60 to 80 percent of Bayer process red mud subjected to microwave-ultrasonic wave synergistic activation treatment, 10 to 25 percent of superfine slag powder, 2 to 8 percent of nano SiO2 and 1 to 5 percent of mixture of sodium lignin sulfonate and ammonium formate, the parameters of the microwave-ultrasonic wave synergistic activating treatment are as follows: the microwave power is 600 to 1000W, the ultrasonic wave frequency is 30 to 50kHz, and the treatment time is 20 to 40min. Compared with an existing technology of only microwave single activation or red mud-bentonite compounding, in the embodiment of the invention, microwave-ultrasonic wave synergistic activation and a mixture of superfine slag powder-nano SiO2-sodium lignin sulfonate and ammonium formate are introduced into the red mud-based binder in a ternary synergistic manner for the first time; and the problems of activity, strength and grade loss are synchronously solved on the premise of not introducing bentonite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of metallurgical binder technology, and particularly relates to Bayer process red mud-based composite pellet binders and their preparation methods, as well as iron ore pellets. Background Technology

[0002] Bayer process red mud is a major solid waste generated by the aluminum industry. For every ton of alumina produced, 0.8-1.5 tons of red mud are generated, with a pH of 10-13. Its storage occupies land and causes soil alkalization and heavy metal pollution. Red mud contains iron oxide, alumina, silica, and calcium and magnesium oxides, and has resource potential. Pellet production requires binders to ensure strength. Traditional bentonite contains silica gangue, which reduces the grade of the mineral powder and is costly. Existing red mud-bentonite composite binders still introduce bentonite, failing to solve the grade reduction problem; microwave activation of red mud alone offers limited activity improvement and does not synergize with mixtures of slag powder, nano-SiO2, sodium lignosulfonate, and ammonium formate. Summary of the Invention

[0003] This application provides Bayer process red mud-based composite pellet binder and its preparation method, as well as iron ore pellets, to solve the following technical problem: how to prepare high-performance composite pellet binder using Bayer process red mud as raw material.

[0004] In a first aspect, embodiments of this application provide a Bayer process red mud-based composite pellet binder, composed of the following components by mass fraction: The mixture consists of 60%-80% Bayer process red mud, 10%-25% slag powder, 2%-8% nano-SiO2, and 1%-5% sodium lignosulfonate and ammonium formate, all activated by microwave-ultrasound synergistic treatment. The parameters for the microwave-ultrasound synergistic activation treatment are: microwave power 600-1000W, ultrasonic frequency 30-50kHz, and treatment time 20-40min.

[0005] Optionally, the specific surface area of ​​the slag powder is 400-500 m². 2 / kg and particle size ≤5μm.

[0006] Optionally, the average particle size of the nano-SiO2 is 20-50 nm and the purity is ≥99 wt%.

[0007] Optionally, the total mass fraction of free CaO and Al2O3 in the Bayer red mud treated with microwave-ultrasound synergistic activation is increased by ≥15% compared with that of unactivated Bayer red mud.

[0008] Optionally, the mass ratio of sodium lignosulfonate to ammonium formate is 1:1.

[0009] Secondly, embodiments of this application provide a method for preparing the Bayer process red mud-based composite pellet binder according to any one of the first aspects, the method comprising: The Bayer process red mud is screened to remove particles with a diameter >100μm, resulting in fine red mud powder; Fine red mud powder is treated with microwave power of 600-1000W and ultrasonic frequency of 30-50kHz for 20-40 minutes to obtain activated red mud. The activated red mud, slag powder, nano-SiO2, sodium lignosulfonate and ammonium formate are mixed according to the mass fractions and stirred at 300-500 r / min for 15-25 min to obtain Bayer process red mud-based composite pellet binder.

[0010] Optionally, the screening is performed using a 140-160 mesh vibrating screen.

[0011] Optionally, the stirring is carried out at an ambient temperature of 20-30℃ and a relative humidity of 40%-60%.

[0012] Thirdly, embodiments of this application provide an iron ore pellet, which is made by uniformly mixing iron concentrate powder with the Bayer process red mud-based composite pellet binder described in any one of the first aspects, followed by pelletizing, drying and calcination; The amount of Bayer process red mud-based composite pellet binder added is 3%-8% of the iron concentrate powder mass.

[0013] Optionally, the calcination temperature is 1200-1300℃ and the calcination time is 30-60 min.

[0014] Optionally, the iron concentrate powder has a -200 mesh content of ≥80% and an iron grade of ≥65%.

[0015] The technical solutions provided in this application have the following advantages compared with the prior art: Because Bayer process red mud, when used directly as a binder, suffers from insufficient active ingredients, low strength, and large fluctuations in strength, this application's embodiments first treat the Bayer process red mud under microwave power of 600-1000W and ultrasonic frequency of 30-50kHz for 20-40 minutes. The microwave-ultrasonic synergistic activation disrupts the red mud's agglomerate structure and stimulates free CaO and Al2O3, thereby improving the red mud's hydration and gelling ability and reactivity, solving the problem of insufficient active ingredients. Subsequently, using 60%-80% of this activated red mud as a framework, 10%-25% slag powder is introduced; the potential active phase in the slag powder interacts with the active phase released by the activated red mud. Ca2+ Al 3+Synergistic hydration occurs, generating more gelling products to compensate for the strength deficiencies of red mud alone. Then, 2%-8% nano-SiO2 is added; the high specific surface area of ​​nano-SiO2 fills the interparticle gaps and reacts with Ca(OH)2 to generate additional CSH gel, thereby enhancing the interparticle interface bonding force and further stabilizing the strength. Finally, a mixture of 1%-5% sodium lignosulfonate and ammonium formate is added; the dispersion and water-reducing effects of the mixture improve the fluidity of the mixture, ensuring uniform distribution of each component and eliminating compositional fluctuations. The above four components, in the stated proportions, form a progressive chain of "activation-synergy-filling-dispersion," resulting in a binder green pellet drop strength ≥4 times / 0.5m, a calcined compressive strength ≥180N / pellet, and reduced impact on ore powder grade, thus preparing a high-performance composite pellet binder using Bayer process red mud as raw material. Compared to existing technologies that only use microwave single activation or red mud-bentonite compounding, this application's embodiment is the first to combine microwave-ultrasound synergistic activation with slag micropowder-nano-SiO2. 2- A mixture of sodium lignosulfonate and ammonium formate is synergistically introduced into a red mud-based binder to simultaneously address the issues of activity, strength, and grade loss without introducing bentonite. Detailed Implementation

[0016] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0017] The range descriptions used herein, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values ​​within that range. For example, the range descriptions of "1 to 6" or "1~6" cover all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the terms "including" and "contains" as used herein mean "including but not limited to"; relational terms such as "first" and "second" are used only to distinguish different entities or operations and do not imply an actual order or relationship; "and / or" indicates that multiple situations can exist individually or simultaneously; expressions such as "at least one," "multiple," and "at least one" refer to any combination of the corresponding objects, including combinations of single or multiple objects. The proportional relationships mentioned herein, such as mass ratios and molar ratios, should be understood as the correspondence between the first and second terms of a proportional formula, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained through commercial purchase or prepared using existing methods.

[0018] In a first aspect, embodiments of this application provide a Bayer process red mud-based composite pellet binder, composed of the following components by mass fraction: The mixture consists of 60%-80% Bayer process red mud, 10%-25% slag powder, 2%-8% nano-SiO2, and 1%-5% sodium lignosulfonate and ammonium formate, all activated by microwave-ultrasound synergistic treatment. The parameters for the microwave-ultrasound synergistic activation treatment are: microwave power 600-1000W, ultrasonic frequency 30-50kHz, and treatment time 20-40min.

[0019] Bayer process red mud: refers to solid waste discharged during alumina production, with a pH of 10-13, containing iron oxide, alumina, silica, and calcium and magnesium oxides. Slag powder: refers to granulated blast furnace slag fine powder. Mixture of sodium lignosulfonate and ammonium formate: refers to a powder mixture of sodium lignosulfonate and ammonium formate used as a dispersant-water-reducing agent.

[0020] After microwave-ultrasonic synergistic activation treatment, the internal agglomeration structure of Bayer process red mud is destroyed, and the content of free CaO and Al2O3 active ingredients increases, thereby enhancing the hydration and cementing ability of Bayer process red mud. The slag powder undergoes a synergistic hydration reaction with the free CaO and Al2O3 in the activated Bayer process red mud to generate hydrated calcium silicate and hydrated calcium aluminate cementitious products, thereby improving the strength of the binder. Nano-SiO2 fills the gaps between particles and participates in the hydration reaction, further increasing the amount of cementitious products, thereby improving the interparticle bonding force. The mixture of sodium lignosulfonate and ammonium formate improves the fluidity and dispersibility of the binder, thereby improving the uniformity of mixing the binder and mineral powder. The combined effect of the above factors allows for the preparation of a high-performance composite pellet binder using Bayer process red mud as raw material, solving the technical problems of traditional binders that reduce mineral powder grade and have high costs. Creative approach: For the first time, microwave-ultrasound synergistic activation of Bayer process red mud is combined with a mixture of slag powder, nano-SiO2, sodium lignosulfonate, and ammonium formate in a specific ratio to form a low-grade, high-strength, and low-cost red mud-based composite pellet binder. The mass fraction of Bayer process red mud treated with microwave-ultrasound synergistic activation includes, but is not limited to, 60%, 65%, 70%, 75%, and 80%.

[0021] In some embodiments, the specific surface area of ​​the slag powder is 400-500 m². 2 / kg and particle size ≤5μm.

[0022] The specific surface area of ​​slag powder is 400-500 m². 2The slag powder has a specific surface area of ​​ / kg and a particle size ≤5μm, which increases the contact area between the slag powder and the activated Bayer red mud. This accelerates the hydration reaction between the potential active components in the slag powder and the free CaO and Al2O3 in the activated Bayer red mud, generating more cementitious products and thus improving the strength of the binder. This solves the problem of preparing high-performance composite pellet binders. The specific surface area of ​​the slag powder includes, but is not limited to, 400m². 2 / kg, 420m 2 / kg, 450m 2 / kg, 480m 2 / kg, 500m 2 / kg, etc.

[0023] In some embodiments, the average particle size of the nano-SiO2 is 20-50 nm and the purity is ≥99 wt%.

[0024] The nano-SiO2 has an average particle size of 20-50 nm and a purity ≥99 wt%. This allows the nano-SiO2 particles to fill the gaps between activated Bayer process red mud and slag powder particles, thereby increasing the physical interlocking between particles. The high-purity nano-SiO2 exhibits high surface activity, reacting with free CaO in the activated Bayer process red mud to form hydrated calcium silicate gel, thus increasing the amount of cementitious products and improving the binder strength. This solves the problem of preparing high-performance composite pellet binders. The average particle size of the nano-SiO2 includes, but is not limited to, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm.

[0025] In some embodiments, the total mass fraction of free CaO and Al2O3 in the Bayer red mud treated with microwave-ultrasound synergistic activation is ≥15% higher than that in unactivated Bayer red mud.

[0026] Microwave-ultrasound synergistic activation treatment increases the total mass fraction of free CaO and Al2O3 in Bayer process red mud by ≥15% compared to unactivated Bayer process red mud, thereby significantly increasing the hydration reaction activity of activated Bayer process red mud, generating more hydrated calcium aluminate and hydrated calcium silicate cementitious products, thus improving the early and late strength of the binder, and thus solving the problem of preparing high-performance composite pellet binders.

[0027] In some embodiments, the mass ratio of sodium lignosulfonate to ammonium formate is 1:1.

[0028] At a mass ratio of 1:1, the sulfonic acid groups of sodium lignosulfonate and the carboxylic acid ammonium groups of ammonium formate form a synergistic adsorption-complexion network, thereby simultaneously capturing Ca²⁺ from the slurry. + Al³ + Fe³ +The ions generate soluble chelates, thereby inhibiting the premature consumption of the basicity of the composite activator by free alkali metal ions; the basicity is retained, thereby accelerating the pozzolanic reaction between the slag cement and silica fume in the shell and promoting the densification of CSH gel; the degree of densification of the shell is improved, thereby increasing the compressive strength of the cylinder; at the same time, the soluble chelates are thermally decomposed and volatilized during the steam curing stage without adding extra mass, thus avoiding an increase in bulk density; finally, the technical problem of "how to obtain gradient ceramsite with improved compressive strength but no increase in bulk density using Bayer process red mud without firing" is solved.

[0029] Secondly, embodiments of this application provide a method for preparing the Bayer process red mud-based composite pellet binder according to any one of the first aspects, the method comprising: The Bayer process red mud is screened to remove particles with a diameter >100μm, resulting in fine red mud powder; Fine red mud powder is treated with microwave power of 600-1000W and ultrasonic frequency of 30-50kHz for 20-40 minutes to obtain activated red mud. The activated red mud, slag powder, nano-SiO2, sodium lignosulfonate and ammonium formate are mixed according to the mass fractions and stirred at 300-500 r / min for 15-25 min to obtain Bayer process red mud-based composite pellet binder.

[0030] The Bayer process red mud is sieved to remove particles larger than 100 μm, resulting in fine red mud powder, thus avoiding large particles from weakening the uniformity of the binder. The fine red mud powder is then treated with microwave power of 600-1000 W and ultrasonic frequency of 30-50 kHz for 20-40 min to obtain activated red mud, thereby increasing the content of free CaO and Al2O3. The activated red mud, slag powder, nano-SiO2, sodium lignosulfonate, and ammonium formate are mixed according to their mass fractions and stirred at 300-500 r / min for 15-25 min to ensure uniform dispersion and close contact of the components, promoting subsequent hydration reactions. This process allows for the preparation of a high-performance composite pellet binder using Bayer process red mud as raw material. Stirring speeds include, but are not limited to, 300 r / min, 350 r / min, 400 r / min, 450 r / min, and 500 r / min.

[0031] In some embodiments, the screening is performed using a 140-160 mesh vibrating screen.

[0032] 140-160 mesh vibrating screen: This refers to a vibrating sieving device with a screen aperture size of 100-106μm. The 140-160 mesh vibrating screen ensures complete removal of particles >100μm from Bayer process red mud, guaranteeing that the fine red mud powder particle size is ≤100μm. This improves the efficiency of subsequent microwave-ultrasonic synergistic activation treatment, thereby enhancing the activity of the activated red mud and ultimately solving the problem of preparing high-performance composite pellet binders.

[0033] In some embodiments, the stirring is carried out at an ambient temperature of 20-30°C and a relative humidity of 40%-60%.

[0034] Ambient temperature: refers to the air temperature in the mixing operation area. Relative humidity: refers to the relative humidity of the air in the mixing operation area.

[0035] Stirring is carried out at an ambient temperature of 20-30℃ and a relative humidity of 40%-60%. This avoids rapid moisture evaporation due to high temperatures and prevents a decrease in the dissolution rate of the sodium lignosulfonate and ammonium formate mixture due to low temperatures. This ensures uniform dispersion of all binder components, thereby guaranteeing stable binder performance and solving the problem of preparing high-performance composite pellet binders. Ambient temperatures include, but are not limited to, 20℃, 22℃, 25℃, 28℃, and 30℃.

[0036] Thirdly, embodiments of this application provide an iron ore pellet, which is made by uniformly mixing iron concentrate powder with the Bayer process red mud-based composite pellet binder described in any one of the first aspects, followed by pelletizing, drying and calcination; The amount of Bayer process red mud-based composite pellet binder added is 3%-8% of the iron concentrate powder mass.

[0037] After iron concentrate powder is uniformly mixed with Bayer process red mud-based composite pellet binder, the activated red mud, slag powder, and nano-SiO2 in the Bayer process red mud-based composite pellet binder generate cementitious products in the hydration reaction, thereby firmly binding the iron concentrate powder particles. The green pellets are dried to remove free water, thus maintaining their shape. The green pellets are then calcined to further harden the cementitious products, resulting in high-strength iron ore pellets. The amount of Bayer process red mud-based composite pellet binder added is 3%-8% of the iron concentrate powder mass, thus ensuring strength while avoiding excessive binder that reduces iron grade, thereby solving the application problem of high-performance composite pellet binders. The amount of Bayer process red mud-based composite pellet binder added is, but is not limited to, 3%, 4%, 5%, 6%, 7%, and 8% of the iron concentrate powder mass.

[0038] In some embodiments, the calcination temperature is 1200-1300°C and the calcination time is 30-60 min.

[0039] A roasting temperature of 1200-1300℃ and a roasting time of 30-60 minutes induces a ceramization transformation of the cementitious products in the iron ore pellets, resulting in a dense structure and improved compressive strength. Simultaneously, this temperature range prevents over-roasting, which could lead to softening and deformation of the pellets, thus maintaining dimensional stability and solving the problem of preparing high-performance iron ore pellets. Roasting temperatures include, but are not limited to, 1200℃, 1220℃, 1250℃, 1280℃, and 1300℃.

[0040] In some embodiments, the iron concentrate powder has a -200 mesh content of ≥80% and an iron grade of ≥65%.

[0041] Iron grade: refers to the mass percentage of total iron in iron concentrate powder.

[0042] The iron concentrate powder has a -200 mesh content of ≥80%, which increases the specific surface area of ​​the iron concentrate particles, thereby increasing the contact area with the Bayer process red mud-based composite pellet binder and improving the hydration and cementation effect. The iron grade is ≥65%, ensuring high reduction efficiency of the iron ore pellets during subsequent smelting processes, thus addressing the smelting requirements for high-performance iron ore pellets. The -200 mesh content of the iron concentrate powder includes, but is not limited to, 80%, 82%, 85%, 88%, and 90%.

[0043] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to industry standards. If there is no corresponding industry standard, then generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0044] Example 1 A method for preparing a Bayer process red mud-based composite pellet binder includes the following steps: (1) Pass the Bayer red mud through a 150-mesh vibrating screen to remove particles with a diameter >100μm from the Bayer red mud and obtain fine red mud powder. (2) The fine red mud powder was placed in a microwave-ultrasonic synergistic reactor and treated for 40 min under microwave power of 600W and ultrasonic frequency of 30kHz to obtain activated red mud. (3) A mixture of activated red mud, slag powder, nano SiO2, sodium lignosulfonate and ammonium formate (mass ratio of sodium lignosulfonate: ammonium formate = 1:1) was added to a mixer at mass fractions of 60%, 25%, 8% and 7%, respectively. The mixture was stirred for 25 minutes at a speed of 300 r / min, an ambient temperature of 20℃ and a relative humidity of 40% to obtain Bayer process red mud-based composite pellet binder. (4) Add the Bayer process red mud-based composite pellet binder to the iron concentrate powder at 3% of the iron concentrate powder mass, and mix the iron concentrate powder with the Bayer process red mud-based composite pellet binder to obtain mixed mineral powder; (5) Pelletize the mixed mineral powder to obtain green pellets; (6) Dry the green pellets in a drying oven at 120℃ for 120 min to obtain dried pellets; (7) The dry pellets were roasted at 1200℃ for 60 minutes to obtain iron ore pellets.

[0045] Example 2 A method for preparing a Bayer process red mud-based composite pellet binder includes the following steps: (1) Pass the Bayer red mud through a 150-mesh vibrating screen to remove particles with a diameter >100μm from the Bayer red mud and obtain fine red mud powder. (2) The fine red mud powder was placed in a microwave-ultrasonic synergistic reactor and treated for 30 minutes under microwave power of 800W and ultrasonic frequency of 40kHz to obtain activated red mud. (3) A mixture of activated red mud, slag powder, nano SiO2, sodium lignosulfonate and ammonium formate (mass ratio of sodium lignosulfonate: ammonium formate = 1:1) was added to a mixer at mass fractions of 70%, 20%, 5% and 5%, respectively. The mixture was stirred for 20 minutes at a speed of 400 r / min, an ambient temperature of 25℃ and a relative humidity of 50% to obtain Bayer process red mud-based composite pellet binder. (4) Add the Bayer process red mud-based composite pellet binder to the iron concentrate powder at 5% of the iron concentrate powder mass, and mix the iron concentrate powder with the Bayer process red mud-based composite pellet binder to obtain mixed mineral powder. (5) Pelletize the mixed mineral powder to obtain green pellets; (6) Dry the green pellets in a drying oven at 120℃ for 120 min to obtain dried pellets; (7) The dry pellets were roasted at 1250℃ for 45 minutes to obtain iron ore pellets.

[0046] Example 3 A method for preparing a Bayer process red mud-based composite pellet binder includes the following steps: (1) Pass the Bayer red mud through a 150-mesh vibrating screen to remove particles with a diameter >100μm from the Bayer red mud and obtain fine red mud powder. (2) The fine red mud powder was placed in a microwave-ultrasonic synergistic reactor and treated for 20 min under microwave power of 1000W and ultrasonic frequency of 50kHz to obtain activated red mud. (3) Add the mixture of activated red mud, slag powder, nano SiO2, sodium lignosulfonate and ammonium formate (mass ratio of sodium lignosulfonate: ammonium formate = 1:1) to a mixer at mass fractions of 80%, 10%, 2% and 3%, respectively. Stir the mixture for 15 minutes at a speed of 500 r / min, an ambient temperature of 30℃ and a relative humidity of 60% to obtain Bayer process red mud-based composite pellet binder. (4) Add the Bayer process red mud-based composite pellet binder to the iron concentrate powder at 8% of the iron concentrate powder mass, and mix the iron concentrate powder with the Bayer process red mud-based composite pellet binder to obtain mixed mineral powder. (5) Pelletize the mixed mineral powder to obtain green pellets; (6) Dry the green pellets in a drying oven at 120℃ for 120 min to obtain dried pellets; (7) The dry pellets were roasted at 1300℃ for 30 minutes to obtain iron ore pellets.

[0047] Example 4 A method for preparing a Bayer process red mud-based composite pellet binder includes the following steps: (1) Pass the Bayer red mud through a 150-mesh vibrating screen to remove particles with a diameter >100μm from the Bayer red mud and obtain fine red mud powder. (2) The fine red mud powder was placed in a microwave-ultrasonic synergistic reactor and treated for 35 min under microwave power of 700W and ultrasonic frequency of 35kHz to obtain activated red mud. (3) A mixture of activated red mud, slag powder, nano SiO2, sodium lignosulfonate and ammonium formate (mass ratio of sodium lignosulfonate: ammonium formate = 1:1) was added to a mixer at mass fractions of 65%, 22%, 6% and 7%, respectively. The mixture was stirred for 22 minutes at a speed of 350 r / min, an ambient temperature of 22℃ and a relative humidity of 45% to obtain Bayer process red mud-based composite pellet binder. (4) Add the Bayer process red mud-based composite pellet binder to the iron concentrate powder at 4% of the iron concentrate powder mass, and mix the iron concentrate powder with the Bayer process red mud-based composite pellet binder to obtain mixed mineral powder. (5) Pelletize the mixed mineral powder to obtain green pellets; (6) Dry the green pellets in a drying oven at 120℃ for 120 min to obtain dried pellets; (7) The dry pellets were roasted at 1220℃ for 50 minutes to obtain iron ore pellets.

[0048] Example 5 A method for preparing a Bayer process red mud-based composite pellet binder includes the following steps: (1) Pass the Bayer red mud through a 150-mesh vibrating screen to remove particles with a diameter >100μm from the Bayer red mud and obtain fine red mud powder. (2) The fine red mud powder was placed in a microwave-ultrasonic synergistic reactor and treated for 25 min under microwave power of 900W and ultrasonic frequency of 45kHz to obtain activated red mud. (3) A mixture of activated red mud, slag powder, nano SiO2, sodium lignosulfonate and ammonium formate (mass ratio of sodium lignosulfonate: ammonium formate = 1:1) was added to a mixer at mass fractions of 75%, 15%, 4% and 6%, respectively. The mixture was stirred for 18 minutes at a speed of 450 r / min, an ambient temperature of 28℃ and a relative humidity of 55% to obtain Bayer process red mud-based composite pellet binder. (4) Add the Bayer process red mud-based composite pellet binder to the iron concentrate powder at 6% of the iron concentrate powder mass, and mix the iron concentrate powder with the Bayer process red mud-based composite pellet binder to obtain mixed mineral powder; (5) Pelletize the mixed mineral powder to obtain green pellets; (6) Dry the green pellets in a drying oven at 120℃ for 120 min to obtain dried pellets; (7) The dry pellets were roasted at 1280℃ for 35 minutes to obtain iron ore pellets.

[0049] Comparative Example 1 A comparative method for preparing iron ore pellets includes the following steps: (1) Add bentonite to iron concentrate powder at 3% of the iron concentrate powder mass, mix the iron concentrate powder and bentonite to obtain mixed mineral powder; (2) Pelletize the mixed mineral powder to obtain green pellets; (3) Dry the raw pellets in a drying oven at 120℃ for 120 min to obtain dried pellets; (4) The dry pellets were roasted at 1250℃ for 45 minutes to obtain iron ore pellets.

[0050] Comparative Example 2 A comparative method for preparing iron ore pellets includes the following steps: (1) Add bentonite to iron concentrate powder at 2% of the iron concentrate powder mass, mix the iron concentrate powder and bentonite to obtain mixed mineral powder; (2) Pelletize the mixed mineral powder to obtain green pellets; (3) Dry the raw pellets in a drying oven at 120℃ for 120 min to obtain dried pellets; (4) The dry pellets were roasted at 1200℃ for 60 minutes to obtain iron ore pellets.

[0051] Comparative Example 3 A comparative method for preparing iron ore pellets includes the following steps: (1) Add bentonite to iron concentrate powder at 4% of the iron concentrate powder mass, mix the iron concentrate powder and bentonite to obtain mixed mineral powder; (2) Pelletize the mixed mineral powder to obtain green pellets; (3) Dry the raw pellets in a drying oven at 120℃ for 120 min to obtain dried pellets; (4) The dry pellets were roasted at 1300℃ for 30 minutes to obtain iron ore pellets.

[0052] Comparative Example 4 A comparative method for preparing iron ore pellets includes the following steps: (1) Add 5% of the iron concentrate powder to the unactivated Bayer red mud according to the mass of the iron concentrate powder, and mix the iron concentrate powder with the unactivated Bayer red mud to obtain mixed mineral powder; (2) Pelletize the mixed mineral powder to obtain green pellets; (3) Dry the raw pellets in a drying oven at 120℃ for 120 min to obtain dried pellets; (4) The dry pellets were roasted at 1250℃ for 45 minutes to obtain iron ore pellets.

[0053] Experimental methods for evaluating results: Drop strength test of green balls: Green balls are dropped freely from a height of 0.5m onto a 5mm thick steel plate, and the number of drops that cause the green ball to break for the first time is recorded.

[0054] Determination of compressive strength after roasting: After roasting, the iron ore pellets were kept at a constant temperature of 110℃ for 30 minutes and then removed. Radial pressure was applied at a speed of 10 mm / min using an electronic universal testing machine, and the maximum load when the iron ore pellets broke was recorded.

[0055] Iron grade determination: The total iron content of iron ore pellets was determined according to GB / T6730.5-2016 "Determination of total iron content in iron ore by titration of potassium dichromate reduced by titanium trichloride", and the reduction value of iron grade was calculated.

[0056] Table 1. Results data for both the examples and comparative examples.

[0057] As shown in Table 1, the technological advancements of this application's technical solution include: 1. Significantly improved drop strength of green pellets: Examples 1–5 all achieved 8–10 drops / 0.5 m, which is ≥33% higher than the highest value of 6 drops in Comparative Examples 1–4, indicating that the Bayer process red mud-based composite pellet binder gives green pellets higher impact resistance.

[0058] 2. The compressive strength is greatly improved after calcination: The compressive strength of Examples 1–5 after calcination is 2200–2500 N / piece, which is ≥16% higher than the highest value of 1900 N in Comparative Examples 1–4, proving that the binder can still maintain higher mechanical properties after calcination.

[0059] 3. The reduction in iron grade is significantly reduced: The reduction in iron grade in Examples 1–5 is ≤0.20 percentage points, which is ≥80% less than the lowest value of 1.00 percentage points in Comparative Examples 1–3. This shows that the binder has a smaller impact on the grade of the ore powder, which is beneficial for subsequent smelting.

[0060] 4. Superior overall performance compared to traditional bentonite and unactivated red mud: Comparative Examples 1–3 used bentonite, and Comparative Example 4 used unactivated Bayer process red mud. The green pellet drop strength and compressive strength after calcination were lower than those of the examples, and the reduction in iron content was higher than that of the examples. This indicates that the microwave-ultrasonic synergistic activation treatment and composite formulation are the key to obtaining the above advantages.

[0061] In summary, this application achieves synergistic progress in improving the strength of green and roasted pellets and reducing mineral powder grade loss through the Bayer process red mud-based composite pellet binder and its preparation method, realizing the efficient resource utilization of industrial solid waste and the simultaneous improvement of pellet performance.

[0062] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A bayer process red mud based composite pellet binder characterized by, consists of the following components by mass fraction: Bayer red mud treated by microwave-ultrasonic synergistic activation 60%-80%, slag powder 10%-25%, nano-SiO2 2%-8%, and a mixture of sodium lignosulfonate and ammonium formate 1%-5%; The parameters of the microwave-ultrasonic synergistic activation treatment are: microwave power 600-1000 W, ultrasonic frequency 30-50 kHz, and treatment time 20-40 min.

2. The composite pellet binder of claim 1, wherein The specific surface area of the slag powder is 400-500 m 2 / kg and the particle size is ≤5 μm.

3. The composite pellet binder of claim 1, wherein The average particle size of the nano-SiO2 is 20-50 nm and the purity is ≥99 wt%.

4. The composite pellet binder of claim 1, wherein, The mass ratio of the sodium lignosulfonate to the ammonium formate is 1:

1.

5. A process for the preparation of the binder for the Bayer process red mud based composite pellets as claimed in any one of claims 1 to 4, characterized by, The method comprises: Screening the Bayer red mud to remove particles with a particle size >100 μm to obtain fine red mud powder; Treating the fine red mud powder under the conditions of microwave power 600-1000 W and ultrasonic frequency 30-50 kHz for 20-40 min to obtain activated red mud; Mixing the activated red mud, slag powder, nano-SiO2, and the mixture of sodium lignosulfonate and ammonium formate according to the mass fractions, and then stirring at a rotation speed of 300-500 r / min for 15-25 min to obtain a Bayer red mud-based composite pellet binder.

6. The preparation method according to claim 5, characterized in that, The screening uses a 140-160 mesh vibrating screen.

7. The preparation method according to claim 5, characterized in that, The stirring is performed at an ambient temperature of 20-30 °C and a relative humidity of 40%-60%.

8. Iron ore pellets, characterized in that The Bayer red mud-based composite pellet binder is prepared by uniformly mixing iron ore concentrate powder with the Bayer red mud-based composite pellet binder according to any one of claims 1-4, followed by balling, drying, and calcination; The addition amount of the Bayer red mud-based composite pellet binder is 3%-8% of the mass of the iron ore concentrate powder.

9. The iron ore pellets according to claim 8, characterized in that, The calcination temperature is 1200-1300 °C and the calcination time is 30-60 min.

10. The iron ore pellets according to claim 8, characterized in that, The -200 mesh fraction of the iron ore concentrate powder is ≥80% and the iron grade is ≥65%. The -200 mesh fraction of the iron ore concentrate powder is ≥80% and the iron grade is ≥65%.